Environment and hormone effects on seed biology of kochia (Kochia scoparia) - Khadka, Samida (Kansas State University, 2017)
Understanding the impact of early spring environmental conditions on kochia seed biology as well as time from flowering to seed maturation could suggest effective control practices. Kochia seed accessions were exposed to moisture stress or different phytohormone combinations across a range of temperature conditions to evaluate cumulative seed germination. Base temperature (T[subscript b]) and base water potential (ψb) were determined and used to calculate thermal (TT), hydro (HT), and hydrothermal (HTT) time to describe cumulative percent kochia germination across the environmental conditions. Base temperature was 2.7 C and ψb was -1.70, -1.62, and -0.92 MPa at 11, 6, and 4 C, respectively. To reach 50% cumulative seed germination, more days (2 and 11 d) and more TT (16.7 and 74.8 Cd) were needed as temperature decreased from 11 to 4 C and as water potential decreased from 0.0 to -1.2 MPa. Using the HT and HTT scale helped to account for effect of moisture stress. A small fraction of seeds under low temperature and high moisture stress germinated faster (10% at 6 C and -1.2 MPa) compared to more seed germinated at higher temperature and less moisture stress (91% at 11 C and -0.0 MPa). Addition of abscisic acid (10 µM ABA) decreased germination by 16% at both 23 and 6 C, while addition of gibberellic acid (10 µM GA) increased germination by 14% at both 23 and 6 C. Addition of ABA delayed time to 50% germination at 6 C compared to water, with 3 days or 10 Cd. Similarly, addition of GA shortened time to 50% germination at 6 C as it took 8.9 d and 29.3 Cd as compared to 10 d and 33 Cd in water. Kochia seed development was observed visually in greenhouse conditions after controlled and natural pollination. Kochia flower buds changed color from light green to dark brown by 36 days after pollination (DAP). At 36 DAP, buds had seeds enclosed in them but a germination study showed they were not yet viable. Hence, seed germination decreased and seeds needed more time to accumulate enough thermal and hydro unit before germinating as temperature and moisture stresses increased from 11 to 4 C and -0.0 to -1.2 MPa. We conclude that kochia seeds can germinate under very low temperature and moisture potential. Hence, should be controlled very early in the growing season. Phytohormones ABA and GA decrease and increase the germination of seeds, respectively. Kochia takes more than 36 DAP to produce viable seeds. Information on flower bud changes after pollination have implications for both kochia management and research.
Keywords: Kochia spring emergence